From Minos to Midas : ancient cloth production in the Aegean and in Anatolia (Ancient textiles series, 2010)
Framing the discussion -- Prehistoric textile production on Crete -- Cloth production in the Mycenaean world -- Gordion and Phrygian cloth production -- Comparative textile production and conclusions